The role of tunnelling in the planning and development of infrastructure a world wide view - Ridley, Tony, 1933- (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Compiled for the 9th Australian Tunnelling conference and exhibition: Breaking new ground held on 27-29 August 1996.